2020
DOI: 10.1097/cm9.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Oral contrast agents lead to underestimation of dose calculation in volumetric-modulated arc therapy planning for pelvic irradiation

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Ercan et al [30] also reported statistically significant dose differences between NCCT-and CCT-based plans for both target volumes and critical structures. Jing et al [20] concluded that oral contrast agents caused clinically significant changes in the dose calculations for the targets and critical structures. Rankine et al [13] reported significant dose discrepancy for critical structures, and Burridge et al [34] found a considerable increase in MU settings due to contrast agents presence in CCT images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ercan et al [30] also reported statistically significant dose differences between NCCT-and CCT-based plans for both target volumes and critical structures. Jing et al [20] concluded that oral contrast agents caused clinically significant changes in the dose calculations for the targets and critical structures. Rankine et al [13] reported significant dose discrepancy for critical structures, and Burridge et al [34] found a considerable increase in MU settings due to contrast agents presence in CCT images.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent VMAT study, Jing et al [20] investigated images from 47 rectal cancer patients. The study concluded that contrast material has a significant effect on calculated doses for the target volumes and critical structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jing et al [20] highlighted the underestimation of dose due to intravenous contrast was slight and was moderate due to an oral contrast agent. But, Weber et al [21] reported a slight reduction of dose to the prostate target (0.03-0.14%) and rectum (1.13%) while studying the effects of bladder opacification on dose calculations with a 6-field conformal plan for prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, if the dose calculation is performed in a contrastenhanced CT, there is a concern of dosimetric deviation because the treatment is administered in the absence of contrast. 1,4 In order to avoid this problem, it is a common practice to obtain two CT scans during the same simulation session: one unenhanced and one enhanced. 5 However, it has been described that performing two CT scans during the simulation not only exposes the patient to additional radiation but also reduces the optimisation of resources in the radiation oncology department by extending the simulation time.…”
Section: Introductionmentioning
confidence: 99%